Severe Thrombocytopenia Caused by Piperacillin/Tazobactam: A Case Report - Montezinho, Sara; Oliveira, Miguel; Alves, Manuela (Gazeta Médica, 2021)
Thrombocytopenia is a recognized side effect of various medications, beverages, foods, and herbal remedies. Piperacillin/tazobactam is a beta-lactam/beta-lactamase inhibitor combination with a broad spectrum of antibacterial activity, associated with hematologic adverse such as reversible neutropenia, but Coombs-positive hemolytic anemia and thrombocytopenia are also reported. We report a case of a 73-year-old male patient with severe piperacillin/tazobactam induced thrombocytopenia later confirmed due to re-exposure to the drug.